2014
DOI: 10.3389/fnagi.2014.00302
|View full text |Cite
|
Sign up to set email alerts
|

Alpha and beta EEG power reflects L-dopa acute administration in parkinsonian patients

Abstract: Aim: To evaluate the effect of an acute L-dopa administration on eye-closed resting state electroencephalographic (EEG) activity of cognitively preserved Parkinsonian patients.Methods: We examined 24 right-handed patients diagnosed as uncomplicated probable Parkinson’s disease (PD). Each patient underwent Unified Parkinson’s Disease Rating Scale (UPDRS)-part-III evaluation before and 60 min after an oral load of L-dopa-methyl-ester/carbidopa 250/25 mg. Resting condition eyes-closed EEG data were recorded both … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
49
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(63 citation statements)
references
References 48 publications
7
49
3
Order By: Relevance
“…In the Parkinson's patients, the decrease in beta burst rate was associated with an increase in 437 symptom severity for bradykinesia and postural/kinetic tremor. Such a link between burst rate 438 and bradykinesia is in line with previous studies showing that decreased beta power in the 439 cortex is related to increased bradykinesia (Airaksinen et al, 2012(Airaksinen et al, , 2015Melgari et al, 2014). 440 A reduction in the average PSD is compatible with the reduction in the number of spontaneous 441 high-amplitude bursts as well as a reduction in sustained oscillatory activity.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…In the Parkinson's patients, the decrease in beta burst rate was associated with an increase in 437 symptom severity for bradykinesia and postural/kinetic tremor. Such a link between burst rate 438 and bradykinesia is in line with previous studies showing that decreased beta power in the 439 cortex is related to increased bradykinesia (Airaksinen et al, 2012(Airaksinen et al, , 2015Melgari et al, 2014). 440 A reduction in the average PSD is compatible with the reduction in the number of spontaneous 441 high-amplitude bursts as well as a reduction in sustained oscillatory activity.…”
Section: Discussionsupporting
confidence: 77%
“…Treatments for Parkinson's disease also seems to be effective 22 through modulation of the cortical beta activity. Administration of dopaminergic medication 23 has been shown to increase the cortical beta power in Parkinson's patients (Heinrichs-Graham 24 et al, 2014;Melgari et al, 2014), suggesting that dopamine levels and the cortical beta power 25 are inversely connected. Similarly, Parkinson's patients treated with electrical deep brain 26 stimulation (DBS) showed an increase in cortical sensorimotor beta power following DBS 27 compared to off treatment (Airaksinen et al, 2012;Cao et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…This suggests that PD subjects whose symptoms respond better to dopamine replacement by L-dopa, have a IL of alpha occipital activity more similar to controls and, from this point of view, a functional index of qEEG in PD could be considered a predictive factor of dopaminergic responsiveness. On the other hand, previous studies [5,6] and a recent report [7] demonstrated a relationship between EEG alpha activity and dopaminergic activation.…”
Section: Discussionmentioning
confidence: 90%
“…Indeed, some earlier studies reported on acute Ldopa effects on neural oscillatory activity detected using quantitative EEG (qEEG), indicating an effect on alpha rhythm asymmetrically localized in the occipital cortex regions [5,6]. Recently, L-dopa has been shown to acutely influence eye-closed resting state EEG alpha and beta rhythms [7].…”
Section: Introductionmentioning
confidence: 98%
“…Based on the fact that the CNS uses a multiplexing of different oscillations (Wimmer et al, 2016) and that the phase-locking of slower ongoing oscillations modulates the power of faster oscillations, it is highly conceivable that the EEG “flow signature” will be polyrhythmic and supported by different mechanisms. The role played by theta oscillations modulated by dopamine in the functional synchronization of the hippocampus and the frontal cortex (Benchenane et al, 2011; Fujisawa and Buzsáki, 2011) must be taken into account in the future search of the “flow signature.” In relation to the importance of dopaminergic influence in positive thinking, it is interesting to note that alpha and beta EEG rhythms recorded in the centro-parietal scalp regions of Parkinsonian patient were increased after L-dopa administration (Melgari et al, 2014). …”
Section: How To Catch the Flow With Eeg Dynamicsmentioning
confidence: 99%